Proposed Future Business Strategy in Small Medium Enterprise: Case CV Waroenk Asia Solusindo - Nurlia Roza, Innayah; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2016)
Abstract— Laundry business in Indonesia has been growing so rapid since 2007. Laundry on kilo’s which has become the main business run by CV Waroenk Asia Solusindo has not attractive anymore. Competition, massive new entrants and increasing price of property rent has leave doubts to the company whether they have to stay in laundry on kilo’s or start other laundry segment. With IO model analysis, helped with external analysis through PESTEL and porter five forces, this thesis will help finding attractive segment industry. There are four final solutions suggested as the decision making result from this thesis. First, Waroenk Laundry brand position need brand rejuvenation through marketing strategy and customer relationship management. Dormitory laundry will focus on cooperation with third parties as dormitory management, and works on big quantity laundry project about 100-2000 customers in 1-5 years contract based. Laundry door to door will use sales delivery go around the housing area in specific time for order pickup. Meanwhile laundry exclusive is laundry per pieces services focus on quality, this segment industry is differs with laundry on kilos. Using internal analysis, it will be seen what resources needed by CV Waroenk Asia Solusindo to use the attractive segment industries. SWOT analysis done in this thesis will help to define what strategy needed by CV Waroenk Asia Solusindo in corporate and functional level. Business model canvass will show business process in new industry segment. This strategy is projected with financial projection analysis and economic value added to see strategy plan effectiveness. Keywords: Laundry, business strategy, attractive industry, porter five forces